(untitled) (International Journal of Built Environment and Sustainability, 2019)
Conditional payment such as “pay when paid” or “pay if paid” can create negative chain effect on the parties in construction projects, resulting in delay on the completion of a project, adversarialism and may affect a contractor’s reputation. Asian International Arbitration Centre (AIAC) has launched a standard form of contract which is Construction Industry Payment Adjudication Act (CIPAA) compliance with the aim to reduce payment issues. The aim of the research is to identify whether the clause for “direct payment under CIPAA 2012” of the new AIAC standard form of contract can facilitate problems in direct payment. In achieving the aim of the research, five legal cases were analysed and thirty questionnaires forms were distributed. Legal cases analysis findings highlighted that the major reasons of the direct payment issue being referred to court is due to the validity of the direct payment agreement between the disputant’s parties. Based on the cases heard before CIPAA enactment, the findings show that out of the three cases, the disputants went to litigation because of the legality of direct payment agreements. Most of the agreements were made orally. For cases analysed after CIPAA was enacted, the findings show that the disputant parties do not opt for adjudication and that the main contractors try to mitigate their responsibilities to the employer. The results from the questionnaires distributed established that, the direct payment clause could be successfully adopted for future use of the industry. Eventhough the AIAC standard form of contract has been formally introduced to the industry, but it is not widely used. From the findings of the questionnaire, it shows that with encouragement and support from the industry, direct payment clause of AIAC standard form of contract have the potential in reducing payment issues in the future. With the remodeling of standard form of contracts that are available in construction industry to be CIPAA compliance , it is hoped that this move may scale down the prevalent payment issues in Malaysian construction industry.